DEVELOPING LEADING ECONOMIC INDICATORS FOR EASTERN INDONESIAN ECONOMY - Handoko, Rudi (Badan kebijakan Fiskal, 2017)
The main reason for the construction of the leading indicators for Gross Regional Domestic Product (GRDP) of Eastern Indonesia is the need for macro-economic policy decision making to obtain the up-to-date condition of the GRDP of Eastern Indonesia development. Using the methodology which was used by the OECD, the composite of leading index for GRDP of Eastern Indonesia has built with its components consist of the 24 variables of total 59 variables relevant to the economy of Eastern Indonesia. This study will contribute to knowledge in terms of the methods used would be adapted to the conditions in Indonesia in two unique characteristics of Indonesia. First, this method adjusts the local area economic conditions in Indonesia are very different in each region and secondly, we adjust the unique characteristics of seasonal patterns in Indonesia, namely the moving seasonal such as Chinese New Year and Idul Fitri.